The Preservation and Reuse of Lenticules Extracted via Small Incision Lenticule Extraction (SMILE): A Narrative Review - Yaohua Zhang; Jing Li; Zhiqing Wu; Yong Li; Guoxi Wu; Shengsheng Wei (Bioengineering)
Small-incision lenticule extraction (SMILE) is a safe and effective procedure to correct myopia and myopic astigmatism. The corneal stromal lenticules extracted from SMILE surgery have good light transmission, mechanical properties, and biocompatibility, which are suitable for the treatment of a variety of corneal diseases and can solve the problem of donor cornea shortage. At present, no single method of preserving corneal stromal lenticules has been universally accepted as ideal, as the preservation of tissue integrity, optical transmittance, cellular viability, and the potential for long-term storage remain key challenges. Current approaches include short-term preservation methods such as the use of dehydrating agents and Optisol GS, and long-term preservation strategies such as cryopreservation, hydrogel nutrient capsules, and silicone oil. Standardized storage methods can improve the use of SMILE-derived lenticules as a substitute for donor corneal tissue in clinical settings. The reuse of corneal stromal lenticules is a highly regarded research area, especially in hyperopia, presbyopia, keratoconus, and some corneal ulcerative diseases, providing new possibilities for addressing corneal tissue shortage and improving surgical outcomes. Here, we review various preservation methods and clinical applications of SMILE-extracted lenticules, highlighting their potential in addressing corneal tissue shortages and the treatment of a variety of corneal diseases.